Deteksi Sebaran Klorofil-a Untuk Zona Tangkapan Ikan Pelagis Berdasarkan Musim di WPPN-RI 713 - Muhammad Yusuf; Maddatuang Maddatuang; Abdul Malik; Irwansyah Sukri (Seminar Nasional LP2M UNM, 2022)
Abstract.  The condition of water fertility is the most significant factor affecting the presence of fish. it depends on the content of chlorophyll-a. This study aims to detect the distribution of chlorophyll-a for pelagic fishing in Indonesian waters (WPPN-RI 713). Detection of chlorophyll-a can be more easily and efficiently carried out by using remote sensing image analysis processed through a geographic information system (GIS). This technology plays an important role in supporting and covering the shortcomings of conventional chlorophyll-a detection. Spatially, the concentration of chlorophyll-a suitable for pelagic fish is mostly found in coastal areas or river estuaries, in contrast, it is lower towards the sea. Based on the monsoon, the water areas with the appropriate concentration of chlorophyll-a mostly occur in the west monsoon, transition I, and east monsoon. While in transition II there will be a decrease in the area of water with the appropriate concentration of chlorophyll-a.There are many suitable water areas in the Makassar Strait, namely, along the western coast of Kalimantan and South Sulawesi. The results of this study are expected to help support the development of fishery activities and the management of marine resources in WPPN-RI 713. Keywords: Chlorophyll-a, Chl, Pelagic fish, Monsoon, citra MODIS